A complete transition to clean household energy can save one–quarter of the healthy life lost to particulate matter pollution exposure in India. (3rd September 2020) - Conibear, Luke; Butt, Edward W; Knote, Christoph; Lam, Nicholas L; Arnold, Stephen R; Tibrewal, Kushal; Venkataraman, Chandra; Spracklen, Dominick V; Bond, Tami C
Abstract: Exposure to fine particulate matter (PM2.5 ) is a leading contributor to the disease burden in India, largely due to widespread household solid fuel use. The transition from solid to clean fuels in households has the potential to substantially improve public health. India has implemented large initiatives to promote clean fuel access, but how these initiatives will reduce PM2.5 exposure and the associated health benefits have not yet been established. We quantified the impacts of a transition of household energy from solid fuel use to liquefied petroleum gas (LPG) on public health in India from ambient and household PM2.5 exposure. We estimate that the transition to LPG would reduce ambient PM2.5 concentrations by 25%. Reduced exposure to total PM2.5 results in a 29% reduction in the loss of healthy life, preventing 348 000 (95% uncertainty interval, UI: 284 000–373 000) premature mortalities every year. Achieving these benefits requires a complete transition to LPG. If access to LPG is restricted to within 15 km of urban centres, then the health benefits of the clean fuel transition are reduced by 50%. If half of original solid fuel users continue to use solid fuels in addition to LPG, then the health benefits of the clean fuel transition are reduced by 75%. As the exposure–outcome associations are non–linear, it is critical for air pollution studies to consider the disease burden attributed to total PM2.5 exposure, and not only the portion attributed to either ambient or household PM2.5 exposure. Our work shows that a transition to clean household energy can substantially improve public health in India, however, these large public health benefits are dependent on the complete transition to clean fuels for all.